Socio-Technical Analysis of Indonesian Government E-Procurement System Implementation - Fitri Amalia (The Indonesian Journal of Accounting Research, 2016)
Abstract: E-governance has become increasingly important to deliver better public services, and increase public trust. One of Indonesia’s e-government reform initiatives was to improve public spending efficiency through public e-procurement system. It is argued that an effective national e-procurement system will potentially generate great savings in the government expenditure, assist in delivering better public services and increase trust. Despite the reform, Indonesia’s public e-procurement has not been very successful due to socio-economic problems. With a specific focus on e-procurement and the issues of transparency and accountability in Indonesia, this research aims to investigate the role and barriers of information technology in enhancing information transparency and accountability to the public. Actor-network theory and the notion of delegation approach are employed in this research. Six semi-structured interviews were conducted with the developers and management of Indonesia Government e-Procurement System, which includes the e-Procurement Directory staff in the Institution of Government Procurement Policy (IGPP), and the users of an e-procurement system. This research concludes that information technology was delegated to automate the procurement process to increase transparency, accountability and prevent fraud. However, barriers of e-literacy, lack of leadership, a reluctance of implementation, and lack of infrastructure created obstacles to attain the goals. This infers that social and technical aspects are interrelated and empower each other to support the technology in enhancing information transparency and accountability. This research suggests that there should be an increased collaborative approach between the developers and users in the application development and implementation to improve e-procurement system implementation to achieve transparency and accountability.Abstrak: E-governance telah menjadi semakin penting untuk memberikan layanan publik yang lebih baik, dan meningkatkan kepercayaan publik. Salah satu inisiatif reformasi e-government Indonesia adalah untuk meningkatkan efisiensi belanja publik melalui sistem e-procurement publik. Dikatakan bahwa sistem e-procurement nasional yang efektif akan berpotensi  menghasilkan  penghematan  besar  dalam  pengeluaran  pemerintah, membantu dalam memberikan layanan publik yang lebih baik dan meningkatkan kepercayaan. Meskipun reformasi, e-procurement publik Indonesia belum berhasil karena masalah sosial-ekonomi. Dengan fokus khusus pada e-procurement dan isu transparansi dan akuntabilitas di Indonesia, penelitian ini bertujuan untuk menyelidiki peran dan hambatan teknologi informasi dalam meningkatkan transparansi informasi dan akuntabilitas kepada publik. Teori jaringan aktor dan gagasan pendekatan delegasi digunakan dalam penelitian ini. Enam wawancara semi-terstruktur dilakukan dengan pengembang dan manajemen Sistem e-Procurement Pemerintah Indonesia, yang mencakup staf Direktori e-Procurement di Lembaga Kebijakan Pengadaan Pemerintah (LKPP), dan pengguna sistem e-procurement. Penelitian ini menyimpulkan bahwa teknologi informasi didelegasikan untuk mengotomatiskan proses pengadaan untuk meningkatkan transparansi, akuntabilitas dan mencegah penipuan. Namun, hambatan e-literacy, kurangnya kepemimpinan, keengganan implementasi, dan kurangnya infrastruktur menciptakan hambatan untuk mencapai tujuan. Ini menyimpulkan bahwa aspek sosial dan teknis saling terkait dan memberdayakan satu sama lain untuk mendukung teknologi dalam meningkatkan transparansi informasi dan akuntabilitas. Penelitian ini menunjukkan bahwa harus ada peningkatan pendekatan kolaboratif antara pengembang dan pengguna dalam pengembangan aplikasi dan implementasi untuk meningkatkan implementasi sistem e-procurement untuk mencapai transparansi dan akuntabilitas.